Assessing socio-economic impacts of Lithium-Ion Battery recycling through Multi-Regional Input-Output Analysis - Goeppel, Pascal; Ott, Julius; Zimek, Martina; Baumgartner, Rupert J. (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The expected rise in electromobility and the increasing use of lithium-ion batteries (LIBs) is generating new challenges and opportunities, particularly in the End-of-Life (EoL) management of batteries. One of these challenges are the socio-economic impacts associated with the EoL process steps on which this paper focuses on. With the method of Multi-Regional Input-Output (MRIO) analysis, a selected recycling process route in Europe is assessed regarding socio-economic impacts, first at current demand (baseline scenario) and followed by an upscaled demand. The results provide insight into differences in some socio-economic impact categories, such as employment, vulnerable employment, and worker remuneration. The scale-up scenarios show, among other things, an increase in the workforce and remuneration (positive impact). However, with an increase in vulnerable employment, negative socio-economic impacts are also evident in Europe-centered recycling processes. The results furthermore show that changing recycling processes can lead to sustainability trade-offs. Due to the limited number of indicators in the selected method, it is not possible to provide an overall picture of social impacts. However, this research shows a clear change in the individual impacts, which underlines the need for proactive measures to overcome infrastructure problems, expand recycling capacities, and improve employment conditions in all sectors.